Social Media as a Promotional Media for Garut’s Celebrities During the Covid-19 Pandemic - Zikri Fachrul Nurhadi; Haryadi Mujianto; Livia Ayu Safitri (Jurnal Spektrum Komunikasi, 2023)
The development of communication and information technology has brought society into a new media era where every individual can communicate via the internet. The internet also gave rise to many online-based media, one of which is Instagram which is currently popular. Instagram social media raises many new phenomena, one of which is the celebrity phenomenon. This phenomenon has become a popular trend even. The purpose of this study was to find out the motive and the meaning of the actors of celebgram activities and their benefits as a promotional media on Instagram social media during this pandemic. The research approach used in this research is descriptive qualitative by using phenomenological research methods, so that in this study the priority is based on the experience of the informants. The data entered is data from interviews, observations on the research subject's Instagram account. The results of the study show that the meaning of celebgram activities as promotional media on Instagram social media during a pandemic is interpreted by sources as one of their efforts to be known by people as unique and creative figures through photo activities they upload on Instagram. This is motivated by their desire to share their hobbies and skills. The use of a platform that is easily accessible to all groups is seen by them as useful for getting endorsements, new friends, relations, money and work of course, especially activities during a pandemic, of course, will be different from activities before the pandemic. Keywords: Instagram; Social media; Pandemic; Promotion; Celebgram.